2012
DOI: 10.1111/j.1365-2133.2012.11197.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the management of vitiligo: the European Dermatology Forum consensus

Abstract: The aetiopathogenic mechanisms of vitiligo are still poorly understood, and this has held back progress in diagnosis and treatment. Up until now, treatment guidelines have existed at national levels, but no common European viewpoint has emerged. This guideline for the treatment of segmental and nonsegmental vitiligo has been developed by the members of the Vitiligo European Task Force and other colleagues. It summarizes evidence-based and expert-based recommendations (S1 level)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
352
0
32

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(416 citation statements)
references
References 125 publications
(154 reference statements)
9
352
0
32
Order By: Relevance
“…367 In 2013, a new European Guideline for vitiligo was published, recommending early treatment of small lesions of recent onset and childhood vitiligo with a combination of phototherapy and topical agents. 483 …”
Section: Recommended Treatment Approaches For Vitiligomentioning
confidence: 99%
See 3 more Smart Citations
“…367 In 2013, a new European Guideline for vitiligo was published, recommending early treatment of small lesions of recent onset and childhood vitiligo with a combination of phototherapy and topical agents. 483 …”
Section: Recommended Treatment Approaches For Vitiligomentioning
confidence: 99%
“…Other clinical guidelines that have been informed by the Cochrane systematic review include patient information sites such as the NHS Choices vitiligo module 472 (which was newly developed as a result of the Cochrane review), the BAD guidelines for the management of vitiligo, 434 European guidelines for the management of vitiligo 483 and guidelines on designing and reporting vitiligo trials. 431 Although it is disappointing that the Cochrane systematic review found mainly small, inconclusive, trials covering a host of different interventions, some clinical implications can be drawn:…”
Section: Implications For Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, having dedicated psychologists in dermatology would help reduce the stigma and negative perceptions of mental health and promote the importance of integrated holistic treatment. Guidelines for the management of vitiligo recommend psychological interventions, specifically cognitive behavioural therapy (CBT) [13]. Self-help based on social anxiety associated with living with vitiligo has also been shown to be effective, however further research is required [5].…”
mentioning
confidence: 99%